Letter (copy) : Spanish refugees - Tewson, Vincent
032-0055-001 International HVT/EAB/DB/107 19th May 1939 The Co-operative Wholesale Society Limited, 1, Balloon Street, MANCHESTER 4. Dear Sirs, SPANISH REFUGEES. We have received your letters of the 16th and 17th May regarding the consignments of clothes and footwear which are being forwarded to your depot at Garston for conveying to the order of the International Federation of Trade Unions at Rouen. We regret very much to note that some confusion has arisen with regard to the forwarding address. We have taken this matter up with the Union concerned and they are taking steps to have the matter rectified. We are also endeavouring to get a complete list of the goods which will be going forward to Rouen and as soon as this is to hand we will send you a copy. Yours sincerely, Assistant Secretary. 292/946/32/55